Optimalisasi Sistem Antrian di Farmasi Rawat Jalan Rumah Sakit Grha Permata Ibu dengan Metode Lean Hospital - Rini Alfatiyah; Sofian Bastuti (Industrial Engineering, Faculty of Engineering, Universitas Sebelas Maret, 2022)
Grha Permata Ibu Hospital is one of the major hospitals in Depok with adequate facilities in its services. One of the main factor in hospital services is drug serviceat the pharmacy. Often the problema in drug service is the long waiting time from drug provision, therefore this research was conducted to identify the waste that occurs in drug services in outpatient pharmacies using the Lean Hospital method by making Value Stream Mapping (VSM) and Process Activity Mapping (PAM). This research was also conducted using quantitative research method to see the optimization in the queuing system in drug services in outpatient pharmacies. Meanwhile the resulto f the observation and calculation of the queuing system in drug services at the pharmacy are that the speed of prescription arrival is 0.297 minutes, for the calculation of the speed of prscription sevice is 3.366 minute per patient, the expected waiting time in the system is 0.32 minutes per patient waiting on the queue is 0.029 minutes per patient. Base on the result of the percentage of Process Cycle Efficiency (PCE), it is known that the efficiency of activity time in drug services in outpatient pharmacies has increased 10.8% from the eclusive system. The resulto f these observations made proposal for improvement in drug services in outpatient pharmacies